The origin of the recent swine influenza A(H1N1) virus infecting humans - Владимир Трифонов; Hossein Khiabanian; Benjamin D. Greenbaum; Raúl Rabadán (2009)
Preliminary analysis of the genome of the new H1N1 influenza A virus responsible for the current pandemic indicates that all genetic segments are related closest to those of common swine influenza viruses.